An Economic Model of Mortality Salience in Personal Financial Decision Making: Applications to Annuities, Life Insurance, Charitable Gifts, Estate Planning, Conspicuous Consumption, and Healthcare - James, Russell N. (2018)
The study of personal mortality salience and the denial of death have a long history in psychology leading to the modern field of Terror Management Theory. However, a simple consumer utility function predicts many of the outcomes identified in experimental research in this field. Further, this economic approach explains a range of otherwise unexpected financial decision-making behaviors in areas as diverse as annuities, life insurance, charitable gifts and bequests, intra-family gifts and bequests, conspicuous consumption, and healthcare. With its relevance to such a wide range of personal financial decisions, understanding the impact of mortality salience can be particularly useful to advisors in related fields.